2005
DOI: 10.1158/1055-9965.epi-04-0356
|View full text |Cite
|
Sign up to set email alerts
|

A Correlation Study of Organochlorine Levels in Serum, Breast Adipose Tissue, and Gluteal Adipose Tissue among Breast Cancer Cases in India

Abstract: We used data from a breast cancer pilot study carried out in Kerala, India in 1997, for which organochlorine levels were measured in three biological media, blood serum, breast adipose tissue, and gluteal adipose tissue, of 37 fasting breast cancer cases (pretreatment). Our objective was to investigate the relationships between organochlorine concentrations in different biological media. Gas-liquid chromatography determined serum, breast adipose, and gluteal adipose tissue levels of dichlorodiphenyltricholoret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 40 publications
4
29
2
Order By: Relevance
“…Levels of DDE in serum and adipose tissue have been shown to be highly correlated in many studies (64). For PCBs this correlation has been less well studied, though it appears to be lower than for DDE (64).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Levels of DDE in serum and adipose tissue have been shown to be highly correlated in many studies (64). For PCBs this correlation has been less well studied, though it appears to be lower than for DDE (64).…”
Section: Discussionmentioning
confidence: 99%
“…Levels of DDE in serum and adipose tissue have been shown to be highly correlated in many studies (64). For PCBs this correlation has been less well studied, though it appears to be lower than for DDE (64). However, correlations among levels of PCBs in serum and breast milk, which have been better-studied, tend to be relatively high, although again correlations for DDE are greater (65).…”
Section: Discussionmentioning
confidence: 99%
“…The partitioning of chemicals between adipose tissue and serum, generally expressed as adipose/serum ratio in published literature (Rusiecki et al, 2005;Stellman et al, 1998;Wolff et al, 1982), is an important parameter used in physiologically based pharmacokinetic models. In our study, the strong associations were found between adipose tissue and matched serum concentrations of all detectable individual compounds except for BDE-209 (Spearman correlation analysis, p<0.001 for each).…”
Section: Adipose-serum Partitioning Of Pcbs and Pbdesmentioning
confidence: 99%
“…The partitioning relationship of a specific compound in adipose tissue and blood is an important parameter employed in physiologically based pharmacokinetic models, and is strongly useful for evaluating the toxicity of chemicals and their health risks to humans. To date, several groups have reported the partition ratio (the ratio equal to adipose tissue concentration divided by its serum concentration) of individual PCB congeners (Rusiecki et al, 2005;Stellman et al, 1998;Wolff et al, 1982). Nevertheless, to the best of our knowledge, no information of PBDEs partitioning relationship is available between adipose tissue and blood in humans.…”
Section: Introductionmentioning
confidence: 99%
“…However, epidemiologic studies concerning exposure to PCB and breast cancer risk have been controversial. Several earlier studies suggested a positive association [38][39][40][41][42][43][44], other studies showed no increased breast cancer risk [45][46][47][48][49][50]. More recent data suggested that the CYP1A1 m2 polymorphisms might add an increased risk to the etiology of breast cancer in women with environmental exposure to PCBs [51].…”
Section: Polychlorinated Biphenylsmentioning
confidence: 99%